Chemical and Physical Characteristics in Uncultivated Soils with Different Lithology in Semiarid Mediterranean Clima - Daniel Moraetis; Nikolaos Lydakis-Simantiris; Despina Pentari; Emmanouil Manoutsoglou; Chryssa Apostolaki; Vasilios Perdikatsis (Applied and Environmental Soil Science)
The aim of this study is to identify the chemical and physical characteristics in uncultivated soils derived from different parent materials under semiarid Mediterranean climatic conditions which favoured the formation of fragile soils. The current work is of great interest in the agriculture and environmental stakeholders for providing a “benchmark” of undisturbed soil quality regarding organic content and nutrients availability. Principal Component Analysis (PCA) was used as the primary tool to demonstrate the soil quality stage, regarding nutrient availability. The statistical analysis revealed that one of the major physicochemical characteristics such as cation exchange capacity (CEC) is controlled exclusively from mineralogy and not from organic matter. Mineralogy and bulk chemical analysis is directly related to soil parent material lithology. The availability of inorganic nutrients (macro- and micronutrients) is low and relatively identical to most of the soils. PCA shows the unusual correlation of K+ with not only illite content but also the OM in soils. The development of soils which are already of low quality in respect of organic content and nutrients is evident in Crete in most of the 54 samples investigated.